The market for steel in Mexico : by principal markets, 1953-62, and demand projections, 1963-70 - Watkins, Ralph J.; Fuller, Kemp G.; Fisher, Jacob; Surveys & Research Corporation (New York : published for Surveys & Research Corp., Washington, by F.A. Praeger, 1964)
The objective of this study was to prepare independent projections of demand for steel in Mexico, by markets and by products.
Results of a survey made by the Surveys and Research Corporation under contract with the Export-Import Bank of Washington.
Includes bibliographical references.
ne 22/01/2019
Loans
Keywords: Steel industry and trade; Investments, American